No time for play [videorecording] - Carolino, Ditsi; Coronel, Sheila; Anson-Roa, Boots (Manila PCIJ, 1996)
Summary taken from container
Examines the flight of some three to five million Filipino children who are forced to work because of poverty, landlessness and war. They are everywhere - in the cities as well as far-flung villages, laboring in factories, sugarcane plantations, even the depths of mine tunnels. Many of theses children are forced to labor in conditions that are hazardous to their health and development. They work long hours, are exposed to toxic substances, and face the threat of being maimed or killed in work-related accidents.
In English, Tagalog, Cebuano with English subtitles
Cameraman, Romulo Regalado; Music, Ronie Quesada
Narrator, Boots Anson-Roa
Keywords: Child labor -- Philippines .; Child Welfare -- Philippines; Children -- Services -- Philippines